Manajemen Penilaian Hasil Belajar Ranah Kognitif Pendidikan Pancasila dan Kewarganegaraan (PPKn) di Sekolah Dasar - Akhmaliah Siti Nailan; Dedeh Sariah; Badrudin Badrudin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The description of management for assessing learning outcomes in the cognitive domain carried out by teachers is not optimal. It can be seen that teachers in carrying out cognitive assessments are only limited to final tests such as daily tests, Mid-Semester Summative (STS), Final Semester Summative (SAS) and End-of-Year Summative (SAT). The aim of this research is to describe the management of assessing student learning outcomes in the cognitive domain in Civics subjects starting from planning, organizing, implementing, reporting and archiving. The research approach used is a qualitative research approach using qualitative descriptive research methods. Data collection techniques include observation, interviews and documentation. With the research population in class IV SDIT Kayyatal Jihaaz, totaling 17 people. The results of the research showed that the average PPKn score in class IV at SDIT Kayyatal Jihaaz was 86.8, which was classified as very high. This is because it is influenced by two factors, namely internal factors and external factors. The steps in cognitive assessment management are planning, organizing, implementing, monitoring and archiving.